Urea–Zinc Chloride Eutectic Mixture-Mediated One-Pot Synthesis of Imidazoles: Efficient and Ecofriendly Access to Trifenagrel - Higuera, Natalia López; Peña-Solórzano, Diana; Ochoa-Puentes, Cristian (Synlett, 2019)
The low-melting mixture urea–ZnCl2 was evaluated as a novel reaction medium for the synthesis of imidazoles. The reaction between a dicarbonyl compound, ammonium acetate, and an aromatic aldehyde is efficiently catalyzed by the eutectic solvent, yielding a wide variety of triaryl-1H-imidazoles or 2-aryl-1H-phenanthro[9,10-d]imidazoles in good to excellent yields. In addition, the eutectic solvent was reused in five cycles without loss of its catalytic activity. This protocol was further explored for the synthesis of the drug trifenagrel, giving an excellent yield.
Keywords: imidazoles; deep eutectic solvent; multicomponent reaction; trifenagrel; phenanthroimidazoles